Analysis of the Influence of Social Media Marketing and E-Wom on Purchase Intention of Somethinc Products Mediated by Brand Trust in Solo Raya - Az-zhahra Ramadhani Margitarino; Sri Murwanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of Social Media Marketing and electronic Word of Mouth (e-WOM) on Purchase Intention for Somethinc products, with Brand Trust as a mediating variable in the Solo Raya region. Using a quantitative approach, data were collected via an online questionnaire from 178 individuals who had previously purchased Somethinc products, selected through purposive sampling, and analyzed using Smart PLS 4.0 software. The study acknowledges that purposive sampling may introduce bias by excluding non-customers, and future research should include broader demographics to capture a comprehensive view of consumer behavior. While the sample size was adequate, expanding it in future studies would enhance generalizability. Social Media Marketing was measured through content consistency, interactivity, and customer engagement on platforms like Instagram and TikTok, while e-WOM was assessed via online reviews, recommendations, and discussions. Results indicate that both Social Media Marketing and e-WOM significantly and positively affect Purchase Intention, directly and indirectly via Brand Trust. To enhance Purchase Intention, Somethinc should prioritize consistent, engaging content, active customer feedback responses, and environmentally sustainable marketing strategies.